2003
DOI: 10.1590/s0004-282x2003000500007
|View full text |Cite
|
Sign up to set email alerts
|

A dual action of alpha-lipoic acid in the brain: an electrophysiological evaluation

Abstract: -Oxidative stress causes metabolic and structural abnormalities during reperfusion. In an animal model of electrophysiological evaluation of cerebral ischemia-reperfusion, α-lipoic acid effect on the oxidative stress was studied by mean absolute amplitude of EEG spectra evaluation. The left carotideal infusion of 3.03 mM α-lipoic acid in Wistar rats after cerebral ischemia and reperfusion caused initial reduction and partial final recuperation of the various EEG spectral frequency mean absolute amplitudes (p<0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…It has shown promise in treating ischemia-reperfusion. Interestingly, both Cardoso do Vale [52] and Schonheit [53] reported a dose response threshold for ALA similar to the therapeutic window noted above in the Giamattei and Altschule trials. Cardoso do Vale found 6.06 mM ALA to be the most therapeutic dose but concluded that at both lower (3.03 mM) and higher (60.6 mM) levels ALA had a pro-oxidant effect.…”
Section: Discussionsupporting
confidence: 58%
“…It has shown promise in treating ischemia-reperfusion. Interestingly, both Cardoso do Vale [52] and Schonheit [53] reported a dose response threshold for ALA similar to the therapeutic window noted above in the Giamattei and Altschule trials. Cardoso do Vale found 6.06 mM ALA to be the most therapeutic dose but concluded that at both lower (3.03 mM) and higher (60.6 mM) levels ALA had a pro-oxidant effect.…”
Section: Discussionsupporting
confidence: 58%
“…Similarly, ALA has been shown to exert a neuroprotective effect in several in vivo models of neurologic injury, such as traumatic brain injury [22], cerebral ischemia [23], seizures [24] and autoimmune encephalomyelitis [25].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that LA exerts powerful anti-oxidant effects, which has led to studies of the use of LA in a number of oxidative stress conditions [11] . Previous studies have shown that LA can ameliorate I/R injury in organs such as the brain [12] . In this study, we investigated the effect of LA administration on neurological injury using a rat infrarenal abdominal aortic clamping model.…”
mentioning
confidence: 99%